2018
DOI: 10.1080/13880209.2017.1421672
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of MOTILIPERM in varicocele-induced oxidative injury in rat testis by activating phosphorylated inositol requiring kinase 1α (p-IRE1α) and phosphorylated c-Jun N-terminal kinase (p-JNK) pathways

Abstract: Context: MOTILIPERM was prepared as a mixture of extracts of three medicinal herbs [roots of Morinda officinalis How (Rubiaceae), outer scales of Allium cepa L. (Liliaceae) and seeds of Cuscuta chinensis Lamark (Convolvulaceae)].Objective: To investigate the role of reactive oxygen species (ROS)-based endoplasmic reticulum (ER) stress in a rat model of varicocele and the therapeutic efficacy of MOTILIPERM in this model.Materials and methods: Sixty male rats were divided into five experimental groups: a normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(66 citation statements)
references
References 39 publications
12
51
0
Order By: Relevance
“…A study by Kim et al [13] reported that repetitive cycle of testicular hyperthermia leads to ER stress associated apoptosis of spermatocytes in mouse testis by activation of IRE1-JNK and PERK pathway. In support of these observation, recent study from our lab report varicoceleinduced infertility in rat model by ROS-dependent ER stress in testis [35]. In a study on testicular injury after torsion/detorsion in rat model reported the germ cell apoptosis in testis by upregulate eIF2α and CHOP, which insight the role of ER stress in testicular ischemia/reperfusion injury [45].…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 70%
See 1 more Smart Citation
“…A study by Kim et al [13] reported that repetitive cycle of testicular hyperthermia leads to ER stress associated apoptosis of spermatocytes in mouse testis by activation of IRE1-JNK and PERK pathway. In support of these observation, recent study from our lab report varicoceleinduced infertility in rat model by ROS-dependent ER stress in testis [35]. In a study on testicular injury after torsion/detorsion in rat model reported the germ cell apoptosis in testis by upregulate eIF2α and CHOP, which insight the role of ER stress in testicular ischemia/reperfusion injury [45].…”
Section: Involvement Of Endoplasmic Reticulum Stress In Testis and Gementioning
confidence: 70%
“…Oxidative stress elicits a reduction-oxidation (redox) imbalance [33]. Alteration of redox homeostasis in ER disturbs ER protein folding and causes ER stress, and accumulation of ROS in the ER and mitochondria [35]. Furthermore, oxidative protein folding in the ER of eukaryotic cells generates ROS as a byproduct and cause oxidative stress [32].…”
Section: Introductionmentioning
confidence: 99%
“…This elucidated the possible usage of this formula to treat male infertility by preventing apoptosis of sperm. MOTILIPERM is a mixture of three natural extracts of Morinda officinalis How, Allium cepa L., and Cuscuta chinensis Lamark, which is used to treat rheumatoid arthritis and impotence [ 94 ]. Soni et al reported that MOTILIPERM (100, 200 mg/kg for 4 weeks) exerted protective effects in varicocele induced SD rats by improving reproductive organ parameters (left testis weight, sperm motility, sperm count, epididymis motility, vas deferens count, epididymis count, spermatogenic cell density, and the percentage of damage of seminiferous tubule).…”
Section: Plant Extract and Infertilitymentioning
confidence: 99%
“…ROS are the main marker of oxidative stress, but ROS content was difficult to detect in vivo directly. Malondialdehyde (MDA), an end product of lipid hydroperoxide decomposition, is the most frequently measured index of lipid peroxidation, which can indirectly reflect the ROS content (Soni et al, 2018). The other one is reactive nitric species (RNs).…”
Section: Introductionmentioning
confidence: 99%